KAJIAN TENTANG GENDER PERSPEKTIF ISLAM (Studi Analisis Tentang Posisi Perempuan dan Laki-laki dalam Islam) - Asmaret, Desi (IAIN Batusangkar, 2018)
The aim of this study is to find out the position of women and men in Islamic beliefs to encounter the challenges of feminists or feminism who have always questioned the differences in gender roles between women and men who have been considered lame and asismestris. Is this because of a false understanding of the structure of religious teachings normatively or not? The method used was library research with a qualitative approach. The data were collected from the Qur'an and Sunnah of the Prophet, books on gender and sociology and other relevant sources, then analyzing and drawing conclusions qualitatively. The results of the discussion found that differences between women and men were only privileges and groupings. Men and women are clearly different, but this difference is not intended so that each of them looks for their own ways, but to reach each other to achieve one goal, namely the continuity of life and human civilization itself. For this reason, it is recommended that Islamic law researchers reproduce research with a gender analysis perspective. So that the norms and substance of Islamic law are more easily understood and implemented.